2018
DOI: 10.1016/j.foodhyd.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of an α-1, 6-linked galactomannan from natural Cordyceps sinensis

Abstract: An α-1, 6-linked galactomannan was isolated and purified from natural Cordyceps sinensis. The fine structure analysis of this polysaccharide was elucidated based on partial acid hydrolysis, monosaccharide composition, methylation and 1D/2D nuclear magnetic resonance (NMR) spectroscopy. Monosaccharide composition analysis revealed that this polysaccharide was mainly composed of galactose (68.65%), glucose (6.65%) and mannose (24.02%). However, after partial acid hydrolysis the percentages of galactose, glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Table 2 summarizes the major peaks and the corresponding bonding characteristics derived from the FT-IR spectrum of the EPS-LM-1 fraction ( Supplemental Data Figure S2 ). The large absorption peak near 3413 cm −1 was attributed to the -OH stretching vibration of sugar chains [ 17 ]. The weak absorption peaks at 2930 cm −1 and 1638 cm −1 were attributed to C-H stretching vibration and bound water on the sugar chains, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes the major peaks and the corresponding bonding characteristics derived from the FT-IR spectrum of the EPS-LM-1 fraction ( Supplemental Data Figure S2 ). The large absorption peak near 3413 cm −1 was attributed to the -OH stretching vibration of sugar chains [ 17 ]. The weak absorption peaks at 2930 cm −1 and 1638 cm −1 were attributed to C-H stretching vibration and bound water on the sugar chains, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Many experiments have found that Cordyceps-derived polysaccharides have many physiological regulation potentials, including preventing damage of intestinal cells [19] and promoting immunostimulatory activity [20]. In addition, the monosaccharide composition and structure of Cordyceps-derived polysaccharides have also been studied [21], and their adhesive properties have been explored to be used in the maintenance of starch stability [22]. The purpose of this study is to investigate the regulatory effects of C. militaris fruit body, C. militaris-derived polysaccharides, and cordycepin-rich solution on gut microbiota in mice treated with a high-fat diet, and to evaluate the potentials of C. militaris-derived polysaccharides as a healthy food for improving metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, as shown in Figure 4 A–F, the spectra of MSP1-2 reveal eight residues with signals at δ 5.20/100.9, δ 5.02/102.3, δ 5.08/98.4, δ 4.93/98.7, δ 5.36/99.7, δ 5.31/99.9, δ 5.34/108.4, and δ 5.18/109.5 ppm labeled as A–H. The monosaccharide composition, methylation analysis results, and chemical shifts of the abovementioned anomeric protons and anomeric carbons indicate that residues A–F possess α-configurations, and that residues G and H are present in β-configurations [ 20 , 21 ]. The COSY, HSQC, HMBC, and 1D spectra and methylation results were compared with the reported data for similar glycosyl substitutions [ 20 , 22 ], and the corresponding 1 H and 13 C chemical shifts in MSP1-2 are given in Table 2 .…”
Section: Resultsmentioning
confidence: 99%